2015
DOI: 10.1128/jvi.00262-15
|View full text |Cite
|
Sign up to set email alerts
|

The Minor Capsid Protein VP11 of Thermophilic Bacteriophage P23-77 Facilitates Virus Assembly by Using Lipid-Protein Interactions

Abstract: Thermus thermophilus bacteriophage P23-77 is the type member of a new virus family of icosahedral, tailless, inner-membranecontaining double-stranded DNA (dsDNA) viruses infecting thermophilic bacteria and halophilic archaea. The viruses have a unique capsid architecture consisting of two major capsid proteins assembled in various building blocks. We analyzed the function of the minor capsid protein VP11, which is the third known capsid component in bacteriophage P23-77. Our findings show that VP11 is a dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Extremophilic phages, exemplified by P23-77 from alkaline hot spring and SSIP-1 originating from extreme salinity, may also constitute an important source of novel enzymes for biotechnological applications [10,97]. In addition, the structure of P23-77 suggested mechanisms for stabilization and the assembly of protein-lipid systems at extremely high temperatures [97,138]. In general, an understanding of the mechanistic properties of the membrane-containing virus particles provides interesting new insights into the engineering of tough composite nanomaterials that are well suited to protect fragile cargos [37].…”
Section: Applications Of Membrane-containing Phagesmentioning
confidence: 99%
“…Extremophilic phages, exemplified by P23-77 from alkaline hot spring and SSIP-1 originating from extreme salinity, may also constitute an important source of novel enzymes for biotechnological applications [10,97]. In addition, the structure of P23-77 suggested mechanisms for stabilization and the assembly of protein-lipid systems at extremely high temperatures [97,138]. In general, an understanding of the mechanistic properties of the membrane-containing virus particles provides interesting new insights into the engineering of tough composite nanomaterials that are well suited to protect fragile cargos [37].…”
Section: Applications Of Membrane-containing Phagesmentioning
confidence: 99%
“…Another gene involved in encoding capsid proteins is the minor capsid protein gene. In 2015, Pawlowski et al studied functions of this gene in P23-77 phage 28 . The phage baseplate upper protein gene was also reported by Li et al in ϕ11 genome 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the thermophilic bacteriophage ΦIN93 is the focus of a study to determine its possible use as a VLP (virus-like particle) system for potential biomedical applications [ 38 ]. Specifically, the viral coat proteins ORF13 and ORF14 are of interest, as a previous study has shown that similar proteins from another thermophilic bacteriophage (VP16 and VP17 from the thermophilic bacteriophage P23-77) form complexes when expressed in vitro [ 38 , 43 ]. Overall, truncated versions of ORF13 and ORF14 were able to form ovoid structures that look like VLPs but are smaller than the WT virus, so further research is required [ 38 ].…”
Section: Thermophilic/acidophilic Virusesmentioning
confidence: 99%